2011
DOI: 10.1039/c1nr10884k
|View full text |Cite
|
Sign up to set email alerts
|

Scalable processes for fabricating non-volatile memory devices using self-assembled 2D arrays of gold nanoparticles as charge storage nodes

Abstract: We propose robust and scalable processes for the fabrication of floating gate devices using ordered arrays of 7 nm size gold nanoparticles as charge storage nodes. The proposed strategy can be readily adapted for fabricating next generation (sub-20 nm node) non-volatile memory devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Eah reported the fabrication of 2D highly hcp AuNP monolayer in millimeter‐scale by simple self‐assembly of drying water and toluene droplets with AuNPs at the air‐liquid interface . Muralidharan and co‐workers reported the self‐assembly of AuNP arrays by drop‐casting a colloidal solution on an air‐water interface and then applied such Au monolayer as charge storage nodes to fabricate nonvolatile memory devices . Sashuk and co‐workers reported the fabrication of close‐packed monolayers of charged Janus‐type noble‐metal NPs self‐assembled at the air‐water interface .…”
Section: Self‐assembly Of Nanoparticle At the Air‐liquid Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…Eah reported the fabrication of 2D highly hcp AuNP monolayer in millimeter‐scale by simple self‐assembly of drying water and toluene droplets with AuNPs at the air‐liquid interface . Muralidharan and co‐workers reported the self‐assembly of AuNP arrays by drop‐casting a colloidal solution on an air‐water interface and then applied such Au monolayer as charge storage nodes to fabricate nonvolatile memory devices . Sashuk and co‐workers reported the fabrication of close‐packed monolayers of charged Janus‐type noble‐metal NPs self‐assembled at the air‐water interface .…”
Section: Self‐assembly Of Nanoparticle At the Air‐liquid Interfacementioning
confidence: 99%
“…[61] Muralidharan and co-workers reported the selfassembly of AuNP arrays by drop-casting a colloidal solution on an air-water interface and then applied such Au monolayer as charge storage nodes to fabricate nonvolatile memory devices. [62] Sashuk and co-workers reported the fabrication of close-packed monolayers of charged Janus-type noble-metal NPs self-assembled at the air-water interface. [63] Moreover, Sashuk et al also reported the dynamic self-assembly of a dense monolayer of charged AuNPs with several square centimeters in response to the surface tension gradient.…”
Section: Metal Npsmentioning
confidence: 99%
“…nanoparticles, nanowires/nanotubes, nanoscale films, have been widely studied. Noble metal nanoparticles are the foremost contenders amongst nanomaterials that already have a significant market presence [1], a presence that is more likely to expand as several technologies such as drug delivery [2], nanoelectronics [3], etc. mature in the near future.…”
Section: Introductionmentioning
confidence: 99%
“…15 We aimed to achieve a nanostructured hybrid metal oxide to improve its physical and chemical properties through creating a hollow structure with hierarchical nanostructures, by ion transfer across different solid-solid interfaces in a calcination process. 21,22 However, to the best of our knowledge, there have been no reports on the influence of Gd ion addition on the morphology, size and phase of Mn 3 O 4 nanostructures so far. A thermal decomposition method would be preferable to obtain a void structure by the removal of moisture and gaseous impurities.…”
Section: Introductionmentioning
confidence: 99%